2013
DOI: 10.1073/pnas.1301328110
|View full text |Cite
|
Sign up to set email alerts
|

Citron kinase controls a molecular network required for midbody formation in cytokinesis

Abstract: Cytokinesis partitions cytoplasmic and genomic materials at the end of cell division. Failure in this process causes polyploidy, which in turn can generate chromosomal instability, a hallmark of many cancers. Successful cytokinesis requires cooperative interaction between contractile ring and central spindle components, but how this cooperation is established is poorly understood. Here we show that Sticky (Sti), the Drosophila ortholog of the contractile ring component Citron kinase (CIT-K), interacts directly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
141
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(154 citation statements)
references
References 29 publications
12
141
0
1
Order By: Relevance
“…Indeed, we showed that CIT-K loss alters midbody microtubule stability in sensitive cells, whereas the stability of microtubules affects the sensitivity of cytokinesis to CIT-K loss (Figure 2). In addition to the previous studies implicating CIT-K in actindependent midbody stabilization, 23,25,53 these results add strong support the notion that CIT-K plays a crucial role in the crosstalk between actin and microtubules responsible for the maturation of midbody that precedes abscission. [23][24][25]54 The activity of CIT-K on microtubule stability is most likely independent from the reported interaction between CIT-K and KIF14.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Indeed, we showed that CIT-K loss alters midbody microtubule stability in sensitive cells, whereas the stability of microtubules affects the sensitivity of cytokinesis to CIT-K loss (Figure 2). In addition to the previous studies implicating CIT-K in actindependent midbody stabilization, 23,25,53 these results add strong support the notion that CIT-K plays a crucial role in the crosstalk between actin and microtubules responsible for the maturation of midbody that precedes abscission. [23][24][25]54 The activity of CIT-K on microtubule stability is most likely independent from the reported interaction between CIT-K and KIF14.…”
Section: Discussionsupporting
confidence: 81%
“…A second conclusion of our study is that midbody microtubules are a primary target of CIT-K in abscission control. Although the involvement of CIT-K in events related to microtubule dynamics has previously been suggested, 25,52 we provide for the first time evidence of a direct functional role. Indeed, we showed that CIT-K loss alters midbody microtubule stability in sensitive cells, whereas the stability of microtubules affects the sensitivity of cytokinesis to CIT-K loss (Figure 2).…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations